Analysis of the Implementation of the Hospital Occupational Safety and Health Management System (SMK3RS) in East Java (A Case Study of Regional General Hospitals) - Mokhamad Lutfi Suryo Raharjo; Fourry Handoko; Renny Septiari (International Journal Labs, 2026)
Hospitals are high-risk workplaces that require a comprehensive Occupational Safety and Health Management System (SMK3RS) to protect healthcare workers, patients, visitors, and the hospital environment. This study aims to analyze the implementation of SMK3RS at Karsa Husada Regional General Hospital, Batu City, East Java, with a focus on hazard identification, risk assessment, and risk control in three priority units: CSSD and Laundry, Hospital Facilities and Infrastructure Management Unit (IPSRS), and the Laboratory and Blood Bank Unit (BDRS). This research employed a case study approach involving 70 workers, with 60 respondents selected through stratified random sampling using the Slovin formula. Data were collected through questionnaires, in-depth interviews, focus group discussions, and document analysis. Instrument reliability was tested using Cronbach’s Alpha (? > 0.70). Hazard and risk analysis were conducted using Job Safety Analysis (JSA), Hazard Identification, Risk Assessment, and Risk Control (HIRARC), and Failure Mode and Effect Analysis (FMEA). The results showed that the Laboratory and BDRS unit had the highest risk exposure, with two activities categorized as extreme risk, while the IPSRS unit had one extreme-risk activity related to working at heights without adequate PPE. Eight failure modes were identified as priority hazards requiring immediate control. Recommended corrective actions were formulated based on the Hierarchy of Controls, including elimination, substitution, engineering controls, administrative controls, and PPE compliance. In conclusion, the implementation of SMK3RS at the hospital still requires strengthening, particularly in high-risk units, to improve occupational safety performance and compliance with Minister of Health Regulation No. 66 of 2016.